To know for inform: History and environment in Rondônia - Filho, Lourival Inácio; Alves da Silva, Adalberto; da Cunha, Edivan Carlos; Marques Freire Cunha, Elise; Rebolças Sampaio, Fernando Antônio; Alves Lima Júnior, Gilmar; Giacon, Jones Fernando (Guará Journal, 2025)
The study aimed to reflect the human action on the Environment and the sociocultural formation of Rondônia, a new state although the human presence dates back to thousand years. “Modernization” and “civilization” personified in fortifications, telegraph, railroad, urbanism, industry, and hydroelectrics. Worked in a interdisciplinary way the historical patrimony and the environmental issue. We performed field lessons, phisicochemical analysis of water and soil of the major rivers and historic environments. We created a website and a short movie, detected the neglect in those locations, drinkable water and soil with moderate to high acidity. Mainly, awaken feelings of territoriality in the involved students.